In search of transcendence : Kierkegaard, Wittgenstein, Kazantzakis - Gill, Jerry H. (Value Inquiry Book Series, 2017)
This book explores the philosophical/religious thought of Soren Kierkegaard, Ludwig Wittgenstein, and Nikos Kazantzakis in relation to the concept of transcendence. Each of these thinkers has made a strong impact on Western religious and philosophical thought, but each from a nearly completely different angle as well as from a different national background. This comparative study therefore crosses both national and perspectival boundaries. Each of the three thinkers struggled with the notion of transcendence but in uniquely distinct fashion. The conclusion offers yet a third model, the author's, for understanding transcendence focusing on the concept of "mediation".